Persistent Facial Flushing in a Patient with Telangiectasia Macularis Eruptiva Perstans: An Unusual but Should Emphasized Clinical Finding - He X; Wang B; Jia X; Li Y; Yan H; Mu Q; Chen S (Dove Medical Press, 2022)
Xigetu He,1,* Bailing Wang,1,* Xiujuan Jia,1 Yanfei Li,2 Hongxia Yan,1 Qiri Mu,1 Shana Chen3 1Department of Dermatology, International Mongolian Hospital of Inner Mongolia, Hohhot, 010020, People's Republic of China; 2Department of Dermatology, The First Hospital of Hohhot, Hohhot, 010010, People's Republic of China; 3Department of Hematology, International Mongolian Hospital of Inner Mongolia, Hohhot, 010020, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiri Mu, Department of Dermatology, International Mongolian Hospital of Inner Mongolia, China, 83 University East Street, Hohhot, Inner Mongolia, People's Republic of China, Email muqiri28@163.com Shana Chen, Department of Hematology, International Mongolian Hospital of Inner Mongolia, 83 University East Street, Hohhot, Inner Mongolia, People's Republic of China, Email csnxyk@163.comAbstract: Facial flushing is one of the common conditions in dermatology, which affects the aesthetic of patients to a great extent, and even leads to psychological and economic burdens. The most common causes of facial flushing are often inflammatory skin diseases such as rosacea, contact dermatitis, and others, but the facial flushing as a sign can also be the cutaneous manifestation of systemic disease. Telangiectasia macularis eruptiva perstans (TMEP) is a rare disease associated with mast cells. Here, we describe an unusual clinical finding with persistent facial flushing in a patient with TMEP.Keywords: facial flushing, telangiectasia macularis eruptiva perstans, cutaneous mastocytosis, dermoscopy, mast cells